LPD MOBILE APPLICATION AS A DETERMINANT OF INTEREST OF LPD CUSTOMERS WITH TRUST AS A MODERATION VARIABLE - Astawa, I Gede Putu Banu; Sinarwati, Ni Kadek; Adiputra, I Made Pradana; Putra , I Gede Pawana Ngurah (Universitas Pendidikan Ganesha, 2024)
This study aims to determine the determinants of customer interest in the Village Credit Institution (LPD) using LPD Mobile with trust as a moderating variable. This research was conducted on LPDs in Tabanan Regency with a sample of 347 respondents from 8 LPDs that use mobile applications in Tabanan Regency which were analyzed with SEM PLS 3.0. The results showed thatperceived ease of use had a positive effect on customer interest in using the LPD Mobile application. Usability has a positive effect on customer interest in using the LPD Mobile application. Trust cannot moderate the relationship between perceived ease of use and customer interest in using the LPD Mobile application. Trust can strengthen the positive relationship between usability and customer interest in using the LPD Mobile application.